2019
DOI: 10.3390/pathogens8030156
|View full text |Cite
|
Sign up to set email alerts
|

New Taxon-Specific Heterobasidion PCR Primers Detect and Differentiate North American Heterobasidion spp. in Various Substrates and Led to the Discovery of Heterobasidion irregulare in British Columbia, Canada

Abstract: Heterobasidion annosum sensu lato is a species complex of pathogenic white-rot wood decay fungi which cause root and butt rot in conifer and hardwood species across the Northern hemisphere. Annual losses to forest managers are valued in the billions of dollars, due to tree mortality, reduction in timber yield, and wood decay. In North America, H. irregulare and H. occidentale have a partially overlapping host and geographic range, cause similar disease symptoms and produce similar fruiting bodies, making discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In general, most PCR amplifications are carried out with a DNA concentration of 20 ng/mL. Conventional PCR amplifications used to detect Heterobasidion species are carried out with a DNA concentration of 20 pg/mL (Shamoun et al, 2019). However, the LAMP assay tested in our study was found to detect H. annosum with a DNA concentration of 100 pg/mL.…”
Section: Figurementioning
confidence: 78%
See 1 more Smart Citation
“…In general, most PCR amplifications are carried out with a DNA concentration of 20 ng/mL. Conventional PCR amplifications used to detect Heterobasidion species are carried out with a DNA concentration of 20 pg/mL (Shamoun et al, 2019). However, the LAMP assay tested in our study was found to detect H. annosum with a DNA concentration of 100 pg/mL.…”
Section: Figurementioning
confidence: 78%
“…Several fragments of genes have been described for detection of species of Heterobasidion (Fabritius and Karjalainen, 1993;Johannesson and Stenlid, 2003;Linzer et al, 2008;Chen et al, 2014, Chen, 2015Shamoun et al, 2019;Pellicciaro et al, 2021;Yuan et al, 2021). Although the use of PCR techniques is more successful as a method of detection, it still requires specialized equipment and highly trained personnel, and it is difficult and time-consuming to implement the technique in remote areas and ports.…”
Section: Discussionmentioning
confidence: 99%
“…Several fragments of genes have been described for detection of species of Heterobasidion (Fabritius and Karjalainen, 1993;Johannesson and Stenlid, 2003;Linzer et al, 2008;Chen et al, 2014, Chen, 2015Shamoun et al, 2019;Pellicciaro et al, 2021;. Although the use of PCR techniques is more successful as a method of detection, it still requires specialized equipment and highly trained personnel, and it is difficult and time-consuming to implement the technique in remote areas and ports.…”
Section: Discussionmentioning
confidence: 99%
“…Colonies were marked and counted, and three colonies per disc were sub-cultured on 30% malt extract agar (MEA) plates using a sterile scalpel. We used DNA that was collected from each colony as an identification method for Heterobasidion species via a PCR analysis which employed Heterobasidion-specific primers and an established laboratory protocol [44].…”
Section: Study Sitementioning
confidence: 99%
“…The area of the disc that was covered by these colonies was delineated with a marker at each examination time. A sample of each colony per wood disc was obtained with a sterilized surgical needle to confirm the presence of H. occidentale establishment via direct culturing followed by PCR analysis performed on DNA that was extracted directly from fungal colonies growing on 30% MEA [44]. On the final examination (day 12), each wood disc with its delineated and confirmed colonies was photographed with a 30 cm long ruler as a reference.…”
Section: Stump Experiments Sample Analysismentioning
confidence: 99%